Phase Distortion by Linear Signal Transforms - Filbir, Frank; Liehr, Lukas (Frontiers in Applied Mathematics and Statistics, 2020)
In this note we are concerned with the effect of certain linear transformation of a signal f on its phase. We are in particular interested in phase distortions caused by band-limiting operations. The band-limiting operators serve as a motivation for studying the class of phase preserving operators. This class will be completely characterized.